William Eustis papers - Eustis, William, 1753-1825.; Eustis, Benjamin; Eustis, Caroline Langdon, 1781-1865.
Chiefly incoming correspondence from Eustis's years as U.S. secretary of war and minister to Holland. Subjects include the Burr-Clinton controversy, the Louisiana Purchase, Indian affairs, the war between England and France, and relations between the U.S. and the Netherlands. Also includes papers of Eustis's father Benjamin, his wife Caroline Langdon Eustis, and other family members, legal documents, and other papers. Correspondents include John Quincy Adams, Sylvanus Bourne, William C. C. Claiborne, Joshua Clibborn, Henry Dearborn, Alexander Hill Everett, Nathaniel Fellows, Albert Gallatin, Benjamin Homans, Levi Lincoln, Dolley Madison, James Madison, Samuel L. Mitchill, James Monroe, and Robert Smith.
Microfilm edition, in part, available
Microfilm produced of a portion of the collection from the Manuscript Division.
In part, transcripts.
Physician, diplomat, U.S. secretary of war, and representative and senator from Massachusetts.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John Quincy, -- 1767-1848 -- Correspondence; Bourne, Sylvanus, -- 1761-1817 -- Correspondence; Burr, Aaron, -- 1756-1836.; Claiborne, William C. C. -- 1775-1817 -- Correspondence; Clibborn, Joshua -- Correspondence; Clinton, DeWitt, -- 1769-1828.; Dearborn, Henry, -- 1751-1829 -- Correspondence; Everett, Alexander Hill, -- 1790-1847 -- Correspondence; Fellows, Nathaniel, -- 1780- -- Correspondence; Gallatin, Albert, -- 1761-1849 -- Correspondence; Homans, Benjamin, -- 1765-1823 -- Correspondence; Lincoln, Levi, -- 1782-1868 -- Correspondence; Madison, Dolley, -- 1768-1849 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; Mitchill, Samuel L. -- 1764-1831 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Smith, Robert, -- 1757-1842 -- Correspondence; Indians of North America -- Government relations; Louisiana Purchase; France -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- France; Netherlands -- Foreign relations -- United States; United States -- Foreign relations -- Netherlands; Cabinet officers; Diplomats; Physicians; Representatives, U.S. Congress -- Massachusetts; Senators, U.S. Congress -- Massachusetts